MATHEMATICAL MODEL OF SYSTEM ANALYSIS OF TECHNOLOGICAL PROCESSES IN THE FORM OF KEY PRINCIPLES FOR EFFECTIVE DECISION-MAKING - Atajonova, Saidakhon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article considers a mathematical model of system analysis of technological processes as a tool for increasing the efficiency of management decision-making. The proposed approach is based on international principles of system analysis transformation, including target optimization, modeling processes and accounting for uncertainty factors. The model provides the possibility of formalizing complex processes and their structural decomposition, which ensures the development of sound decisions in process technology management. The results obtained can be applied in various industries focused on increasing productivity and reducing costs.